Answer:
The value of x that makes the equation equal to 0 is -2.
Explanation:
In order to find this, we first must create the composite function using the designated operation. The operation is addition, so we just add them together.
f(x) + g(x) = (f+g)(x)
(x^2 - 2x) + (6x + 4) = (f+g)(x)
x^2 + 4x + 4 = (f+g)(x)
Now, in order to find when this is equal to 0, we need to factor.
x^2 + 4x + 4 = 0
(x + 2)(x + 2) = 0
When it is fully factored, we can set each parenthesis equal to 0 in order to find the value. Since the parenthesis are exactly the same, we only have to do this once.
x + 2 = 0
x = -2